2010
DOI: 10.1074/jbc.m110.137885
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Reactive Oxygen Species Production and Chlamydial Infection by the Mitochondrial Nod-like Family Member NLRX1

Abstract: Chlamydia trachomatis infections cause severe and irreversible damage that can lead to infertility and blindness in both males and females. Following infection of epithelial cells, Chlamydia induces production of reactive oxygen species (ROS). Unconventionally, Chlamydiae use ROS to their advantage by activating caspase-1, which contributes to chlamydial growth. NLRX1, a member of the Nod-like receptor family that translocates to the mitochondria, can augment ROS production from the mitochondria following Shig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 40 publications
(45 reference statements)
4
118
1
Order By: Relevance
“…6,7 Although our findings indicate that NOD5 deficiency does not affect TNF-induced signalling, the confirmation of UQCRC2 as a 'bonafide' interaction partner of NOD5 is consistent with the proposed link between NOD5 and ROS generation. 3,4,8 Mitochondrial ROS has been recently shown to trigger NLRP3 inflammasome activation, and thus modulation of ROS would be an attractive function of NOD5. With the availability of NOD5-deficient mice, this hypothesis is now testable.…”
mentioning
confidence: 99%
“…6,7 Although our findings indicate that NOD5 deficiency does not affect TNF-induced signalling, the confirmation of UQCRC2 as a 'bonafide' interaction partner of NOD5 is consistent with the proposed link between NOD5 and ROS generation. 3,4,8 Mitochondrial ROS has been recently shown to trigger NLRP3 inflammasome activation, and thus modulation of ROS would be an attractive function of NOD5. With the availability of NOD5-deficient mice, this hypothesis is now testable.…”
mentioning
confidence: 99%
“…More recently, other authors also have demonstrated that infection with C. trachomatis elicits the production of ROS [103,104]. These data and the fact that C. trachomatis infection has been associated with a raised leukocyte count and the presence of damaged spermatozoa in semen (see precedent sections), indicate that C. trachomatis might have a role in male infertility trough the production of ROS.…”
Section: Oxidative Stressmentioning
confidence: 81%
“…However, unlike the situation in insects [33], there is no evidence that viral siRNAs are produced in RNA virus-infected mammalian cells. Ding also spoke about the impact that influenza replication in mammalian cells has on cellular miRNAs.…”
Section: Kshv and Innate Immunitymentioning
confidence: 94%